Characterization of Five Natural Anthraquinone Compounds as Potent Inhibitors against CYP1B1: Implications for Cancer Treatment - Chen, Zujia; Xu, Zhixiang; Chen, Xiaodong; Guan, Xintong; Du, Jie; Zhang, Jiahui; Wang, Changyuan; Wu, Jingjing (Current Drug Metabolism, 2024)
BackgroundHuman cytochrome P450 1B1 (CYP1B1) is an extrahepatic enzyme that is overexpressed in many tumors and is associated with tumor development and acquired resistance. Few studies have reported that anthraquinone compounds have inhibitory activity against the CYP1B1 enzyme. Cassiae semen (Leguminosae) is a well-known traditional Chinese medicine containing more than 70 compounds. The crude extracts and pure compounds of Cassiae semen have been widely used in preclinical and clinical practice for their beneficial effects, such as neuroprotective, hepatoprotective, antimicrobial, antioxidant, and hypotensive effects. Aloe-emodin, chrysophanol, obtusifolin, aurantio-obtusin, and rhein are important active natural anthraquinones in Cassiae semen.ObjectiveAloe-emodin, chrysophanol, obtusifolin, aurantio-obtusin, and rhein have a wide range of pharmacological activities and have been found to have good anti-tumor and antioxidant effects. However, the underlying mechanisms of these pharmacological activities remain poorly understood. This study aimed to investigate the inhibitory effects of five natural anthraquinones on the activity of CYP1B1 and to analyze the structure-activity relationship of these compounds.Materials and MethodsIn this study, 7-ethoxyresorufin O-deethylation (EROD) was used as the fluorescent substrate of CYP1B1 to investigate the inhibition effect, and molecular docking was performed to further determine the structural-activity relationship of the compound molecules.ResultsWe found that aloe-emodin and chrysophanol had strong inhibitory effects on CYP1B1 with IC50 values of 0.28 and 0.34μM, respectively, while obtusifolin and aurantio-obtusin had IC50 values of 0.77μM and 9.11μM, respectively. The structural activity analysis showed that the inhibition strength was related to the position of the hydroxyl group substitution and the number of methoxy group substitutions. Rhein containing one carboxyl group showed the weakest inhibition of 23.72μM. The inhibition kinetics showed that all five compounds belonged to the non-competitive inhibition model. The inhibition kinetics revealed that all five compounds exhibited the non-competitive inhibition model.ConclusionThe present study provided a comprehensive analysis of the inhibitory effects of five natural anthraquinones, namely aloe-emodin, chrysophanol, obtusifolin, aurantio-obtusin and rhein, on CYP1B1 activity, and elucidated the structure-activity relationship. Molecular docking simulations further revealed the specific amino acid residues within the active site of CYP1B1, where these compounds exerted their actions. These findings offer novel insights into investigating the potential antitumor properties of natural anthraquinones.
Keywords: structure-activity relationship